Zoonotic intestinal parasites of carnivores: A systematic review in Iran - Shahabeddin Sarvi (Veterinary World, 2018)
Aim: Parasitic infections, especially of the zoonotic-parasitic type, are the most important health, economic, and social problems in developing countries, including Iran. The aim of this study was to review systematically the available data on gastrointestinal parasites of carnivores in Iran and their ability to infect humans.